A researcher's journey: Exploring a sensitive topic with vulnerable women. Issue 1 (February 2017) - Marsh, Christine A.; Browne, Jenny; Taylor, Jan; Davis, Deborah
Abstract: Background: The conduct of research regardless of the subject or methods employed brings responsibilities and challenges. These are greater when dealing with sensitive topics and vulnerable groups and therefore researchers must navigate a range of complex issues and make choices in relation to practical, ethical and philosophical concerns. While literature dealing with research methodologies and research design may assist to some degree, it cannot provide a clear pathway or template as each research project must respond to a unique set of circumstances. We can however, also learn from sharing our stories and critical reflections on our research processes. Objective: The purpose of this article is to highlight the practical and methodological issues arising from researching a sensitive topic with vulnerable women experiencing an Assumption of Care. Discussion: Research involving topics that are deeply personal and private combined with a vulnerable population can be complex and challenging for the researcher. Although some issues were anticipated from the literature, others encountered in this study were unexpected. Special considerations and prerequisites were necessary to build mutual trust and share power with women who had experienced an Assumption of Care at birth. Narrative Inquiry was a good methodological fit for this study as it privileged the voices of women and insisted that their experiences be considered within the context of their lives. Conclusion: Although Narrative Inquiry is a suitable choice for researching sensitive topics with vulnerable women specific considerations are still required to ensure the benefits of this research for both participants and researchers. Family and Community Service (FACS) have now replaced the formerly known Department of Community Services (DoCS) and in consideration of the timing of this study this article uses the terminology as DoCS.